2021
DOI: 10.14814/phy2.14802
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring lung injury with particle flow rate in LPS‐ and COVID‐19‐induced ARDS

Abstract: In severe acute respiratory distress syndrome (ARDS), extracorporeal membrane oxygenation (ECMO) is a life‐prolonging treatment, especially among COVID‐19 patients. Evaluation of lung injury progression is challenging with current techniques. Diagnostic imaging or invasive diagnostics are risky given the difficulties of intra‐hospital transportation, contraindication of biopsies, and the potential for the spread of infections, such as in COVID‐19 patients. We have recently shown that particle flow rate (PFR) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…To date, both exhaled particles and other volatile compounds have been explored as a diagnostic tool for asthma, 20 chronic obstructive pulmonary disease, 21 sarcoidosis, 22 and pulmonary fibrosis 23 . Our previous studies have also shown that an increased PRF was associated with pathological lung conditions, such as ARDS, 12 including COVID‐19‐induced ARDS, 13 and primary graft dysfunction after lung transplant 14 . The current study showed the impact of the cardiac failure on particles in exhaled air in the absence of respiratory pathologies during MV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, both exhaled particles and other volatile compounds have been explored as a diagnostic tool for asthma, 20 chronic obstructive pulmonary disease, 21 sarcoidosis, 22 and pulmonary fibrosis 23 . Our previous studies have also shown that an increased PRF was associated with pathological lung conditions, such as ARDS, 12 including COVID‐19‐induced ARDS, 13 and primary graft dysfunction after lung transplant 14 . The current study showed the impact of the cardiac failure on particles in exhaled air in the absence of respiratory pathologies during MV.…”
Section: Discussionmentioning
confidence: 99%
“…11 We have shown previously that PFR increases in the early stages of acute respiratory disorder syndrome (ARDS) in a porcine ARDS model 12 as well as in extra-corporeal membrane oxygenation models. 13 In preclinical settings using ex vivo lung perfusion, we have shown that cardiac output is correlated to PFR. 7 However, there are no data regarding PFR in patients with cardiac failure nor on which size distribution of particles can be detected in this patient population.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…We aimed to evaluate proteins in EBP as well as analyzing PFR before and 1 month after surgery and comparing the results between LUAD patients and control patients, thereby evaluating the potential to use EBP and PFR as diagnostic tools. Analyzing EBP and PFR have previously been proven useful in diagnosing and evaluating other pulmonary diseases such as asthma, acute respiratory distress syndrome (ARDS) and primary graft dysfunction (PGD) in lung transplant recipients and in patients with COVID-19 by us and other research groups [10,14,15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%